A causal loop analysis of the austerity policy adopted to address the Euro crisis - effects and side effects. (29th December 2014) - Moradi, Amir; Paulet, Elisabeth
The Euro crisis, consisting of the European banking crisis and the European sovereign debt crisis, has raised a huge amount of uncertainty in the Euro zone and has beset the entire world economic system. To address this concern, the austerity policy, emphasising on a surge in individual and corporate taxations and a decline in government spending, has been adopted by the highly leveraged countries in the Euro zone. This paper aims at analysing the dynamics of the austerity policy and demonstrating its effects and side effects on the EU economy by employing the causal loop diagrams to model parameters involved in it. We conclude that this policy has triggered three economic side effects of rising unemployment rate, economic recession and eroded capital of the EU banks as well as some political side effects, leading to the emergence of the debtor's dilemma and the political crisis in the Euro zone.